Envejecimiento Activo En Las Personas Mayores En El Hogar De La Esperanza Del Municipio De Armenia (Q) (2019)
Over the years, older people decrease their ability to perform basic activities of daily life, which leads to greater dependence and diminishes the conditions of autonomy and therefore affects their state of health. In this project, an internship modality, a program of physical and recreational activities for active aging in institutionalized elderly people was established in a center for the well-being of the elderly in the city of Armenia Quindío, planned based on an initial diagnosis and the particular needs found . The program involved 18 elderly people, aged between 60 and 93 years, who did not perform any physical activity, and the results obtained showed a favorable evolution in terms of the functionality referred to the activities of daily life, which allows to conclude that the proposed intervention allowed to improve and, in specific cases, recover functional abilities in front of essential activities for personal care and autonomy. Likewise, the results obtained in other contexts are remarkable, evidencing better processes of socialization, conservation of cognitive and emotional capacities. These changes allowed to encourage physical activity and recreation, as a habit of healthy living, which allows for an active, dignified and quality of life aging.